2016
DOI: 10.1155/2016/4617983
|View full text |Cite
|
Sign up to set email alerts
|

Review of Preclinical and Clinical Studies of Bone Marrow‐Derived Cell Therapies for Intracerebral Hemorrhage

Abstract: Stroke is the second leading cause of mortality worldwide, causing millions of deaths annually, and is also a major cause of disability-adjusted life years. Hemorrhagic stroke accounts for approximately 10 to 27% of all cases and has a fatality rate of about 50% in the first 30 days, with limited treatment possibilities. In the past two decades, the therapeutic potential of bone marrow-derived cells (particularly mesenchymal stem cells and mononuclear cells) has been intensively investigated in preclinical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 109 publications
1
19
0
Order By: Relevance
“…Importantly, these effects were achieved without changing the mesenchymal stromal cell identity of the cells or impairing their neurotrophic actions. Our results support the utilization of rBM-MSCs for the investigation of preconditioning strategies aimed at improving the efficacy of MSCs-based therapies, especially in preclinical studies in rats, which are still widely used in the field of neural regeneration [3, 28, 30, 83, 92, 93].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Importantly, these effects were achieved without changing the mesenchymal stromal cell identity of the cells or impairing their neurotrophic actions. Our results support the utilization of rBM-MSCs for the investigation of preconditioning strategies aimed at improving the efficacy of MSCs-based therapies, especially in preclinical studies in rats, which are still widely used in the field of neural regeneration [3, 28, 30, 83, 92, 93].…”
Section: Discussionsupporting
confidence: 75%
“…Mesenchymal stromal cells (MSCs), multipotent cells that can be isolated from a wide range of fetal, perinatal, and adult tissues, have emerged as a promising cell type for regenerative medicine [1, 2]. Although MSCs do not differentiate into neurons and glial cells in vivo, they have potent immunomodulatory properties and contribute to neural regeneration in a paracrine manner, which makes them an attractive option for the development of novel therapies for several neurological disorders [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BM mononuclear cells (BMMC) are increasingly used as a cell therapy for a variety of brain injuries including stroke, both in preclinical and clinical settings (Rosado-de-Castro et al, 2016). While the identity of the immune cells within the heterogeneous BMMC pool responsible for the protective effects has not been established, one study showed that BMMC depleted of myeloid cells lost their protective potential after transient MCAo in rats while depletion of the lymphocyte and erythrocyte lineage had no effect (Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have reported beneficial effects of autologous bone marrow-derived mononuclear cells when delivered by lumbar puncture after spinal cord injury or intracerebrally into the motor cortex in ALS patients (Box 2), 73, 74 and clinical trials on bone marrow-derived mononuclear cells have also been initiated on patients with stroke or cerebral palsy. 75–77…”
Section: Clinical Trials Using Immune Cell-based Therapy — Successes mentioning
confidence: 99%